Case series of 331 cases of sugammadex compared to neostigmine in patients under 2 years of age. Issue 6 (29th April 2019) - Franz, Amber M.; Chiem, Jennifer; Martin, Lizabeth D.; Rampersad, Sally; Phillips, Jennifer; Grigg, Eliot B.
Abstract: Background: Sugammadex is a novel neuromuscular blockade reversal agent approved by the Food and Drug Administration in 2015, but little literature exists for patients less than 2 years of age. Aims: The aims of this study were to: describe a cohort of patients 2 years old and younger who received sugammadex; describe any adverse effects of sugammadex in this age group; compare time from end of surgery to out of operating room for sugammadex versus neostigmine; compare time between last dose of neuromuscular blocking drug and reversal; and use train‐of‐four data to assess reversal. Methods: Chart review of the medical record and the anesthesia information system captured all patients in this age cohort who received sugammadex or neostigmine over a two‐year period. Adverse medication events were pulled from a mandatory quality improvement field in the electronic anesthesia record. T‐tests were used for analyses. Results: No adverse effects were reported with 331 doses of sugammadex. The average time in minutes between end of surgery and out of operating room was similar for neostigmine (19.6) versus sugammadex (19.4) (mean difference 0.2, 95% CI −1.5‐1.8, P  = 0.85). The average time in minutes between last dose of neuromuscular blocking drug and reversal agent was longer for neostigmine (103) than for sugammadex (84) (mean difference 19, 95% CI 13‐26, P  < 0.001). Conclusions: Sugammadex administration in this young population did not result in any adverse effects. It appears to be equally effective as neostigmine in patients under 2 years of age.